Experimental study fluidized bed reactor using number hole 8 to see distribution gas fluid pressure - Eswanto, Eswanto; Pinem, Riza Refaya; Suprapto, Suprapto (Jurnal Polimesin, 2023)
Innovations related to fluidization systems using fluidized bed reactor are still needed to be developed in order to improve the fluidization process services for particle in order to produce the right fluid pressure in certain fluidized bed spaces that are currently operating. In this research, the pressurized fluid in question is air sourced from a compressor which has been arranged in such a way. The aim of the research is to obtain information regarding the characteristics of bubble resulting from the air pressure process pressing fluidized system particle. The research method was carried out by experimenting with testing fluidized bed reactor as test model in the form 8 hole, providing air pressure from compressor then observing the characteristics visually. The results of this visually documented research have been carried out and obtained. By using the number of hole 8 with height silica sand inserted to height of 25 cm, which is measured from the beginning of the hole plate before pressure is applied. After being given high pressure the bed increased to 27.6 cm, the highest bubble diameter was obtained at the input air pressure of 8 bar, which was 3.9 cm, with bed silica sand produced 26.1 cm, where the babble condition began to appear after the 9th second. Other characteristics also obtained reactor temperature of 25.45 °C where this condition is the smallest when compared to other pressure input results, this is because the small input pressure causes the temperature to be low, while the large pressure input temperature becomes higher due to many factor, including friction between silica sand, silica sand collisions, and faster movement of particle material.